Transmission characteristics of linearly polarized light in altostratus help explain “UV-sky-pol” paradox - Zeng, Xiangwei; Zhang, Yan; Chen, Xueye; Sun, Xindong (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
The perception of skylight polarization in the ultraviolet (UV) by some species is surprising, because the degree of polarization (DoP) of light from the clear sky is considerably lower in the UV than in the visible spectral range. This is the so-called “ultraviolet paradox of the perception of skylight polarization (UV-sky-pol paradox)”. To explain the “UV-sky-pol” paradox, we analyzed the polarization retention characteristics of parallel polarized light transmits in altostratus at multiple wavelengths. According to the polarization sensitive bands of flies, honeybee, scarab beetles and spider, the study wavelength was set at 350 nm, and the wavelength of control group was set at 400, 450, 500, 550 and 600 nm, respectively. Then, we used the polarized light Monte Carlo method to simulate the forward transmission of 100 000 parallel polarization photons in altostratus. Calculation results show that the polarization retention characteristics are excellent at the 350 nm wavelength. Finally, we analyzed the transmission characteristics of parallel polarized light passes through a droplet at 0°–15° forward scattering angle. The analysis results show that there have been significant polarization retention channels in the UV band around 350 nm. This study can help to elucidate the “UV-sky-pol” paradox.
Optica Applicata, Vol. 54, 2024, nr 2, s. 129-134
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; polarization; atmospheric scattering; altostratus; UV-sky-pol paradox